Stabilizing the cubic perovskite phase of CsPbI3 nanocrystals by using an alkyl phosphinic acid. Issue 1 (6th December 2016) - Wang, Chujie; Chesman, Anthony S. R.; Jasieniak, Jacek J.
Abstract : Phase-stable perovskite CsPbI3 nanocrystals have been prepared by replacing conventionally used oleic acid with a phosphinic acid in their synthesis. Abstract : CsPbI3 nanocrystals suffer from a facile cubic perovskite to orthorhombic phase transformation, which deteriorates their appealing optoelectronic properties. Here, we report a new colloidal synthesis that replaces the conventionally used oleic acid with an alkyl phosphinic acid to grow high-quality, phase-stable cubic perovskite CsPbI3 nanocrystals.